Social behavior and group growth of finishing pigs with divergent social breeding values - Hong, Joon-Ki; Kim, Ki-Hyun; Song, Na-Rae; Choi, Taejeong; Hwang, Hyun-Su; Lee, Jae-Kang; Eom, Tae-Kyung; Rhim, Shin-Jae (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Behavioral traits of pigs have been shown to be partly under genetic control, which raises the possibility that behavior might be altered by genetic selection, resulting in pigs with better growth performance. Objective: To evaluate the behavior and growth of finishing pigs and investigate pigs selected for high or low social breeding value (SBV) in relation to social behavior and group growth. Methods: Thirty-five females and 35 boars from five positive and five negative SBV groups of finishing pigs were grown from 30 to 90 kg and housed in 10 test pens (3.0 × 3.3 m, 7 pigs/pen). Pigs were recorded with video technology for nine consecutive hours on days 1, 15, and 30 after mixing. Pigs were weighed at approximately 90 kg body weight and the number of days to reach 90 kg was then calculated. Results: The frequency and duration of behaviors were present in the positive and negative SBV groups after mixing. On day 1 after mixing, agonistic behavior was significantly higher (p=0.027) for the –SBV group compared with the +SBV group. Feeding and feeding-together behaviors were significantly higher (p<0.003) in the +SBV group on days 1 and 30 after mixing. Moreover, growth performance to reach 90 kg body weight was significantly faster (p<0.002) in the +SBV group than in the –SBV group. Conclusion: Social interactions, such as feeding-together behavior, among pen mates might affect their growth rate and feed intake. Selection for SBV could be used as an indirect technique for improving growth performance of pigs.